﻿Le vitrail néo-gothique en France au XIXe siècle - Brisac, Catherine (RACAR : Revue d'art canadienne / Canadian Art Review, 1990)
Iconographers, conservators of public monuments, architect, literary and political enthusiasts of the Gothic revival were unanimous in France in the 1830s in supporting restoration of medieval stained glass. Generally in precarious conditions, windows of Gothic churches were fragmentary, darkened, and illegible. Early in the nineteenth century when cathedrals had been refurbished to be opened again for worship, medieval stained glass was repaired rather than restored by glaziers who joined panels or pieces of different provenances within a single window. One of the first restorations in France professedly using medieval stained glass techniques was that of the St. George window in the Cathedral of Clermont-Ferrand in 1836 by local founders of a “painted glass manufactory.” The firm's procedures in reordering elements of the window, in excessive cleaning of old glass or substitution of new pieces became a model, unofficially endorsed by the Office of Religion (l’administration des cultes), for other French workshops. Rearrangements were often ingenious and may be difficult even now for a practiced eye to detect. From motives related to contemporary mentality and/or ignorance of medieval imagery, stained glass workers frequently falsified or transformed the subjects of Gothic windows. An instance was the Clermontois firm's obliteration of historiated medallions in the window of St. Cyprian of Carthage in the Cathedral of Lyon and substitution of a cycle dedicated to founders of the church in Lyon. These practices co-existed with better measures such as the systematic tracing of stained glass prior to restoration adopted at the Cathedral of Le Mans from 1839. Restorations like that of Lyon continued in spite of vigorous criticism from Fathers Cahier and Martin, instructions issued by the Office of Diocesan Buildings in 1848 and creation of the Commission on Stained Glass (1849-53). A late “success” in this line was the reworking of windows in the Chapel of the Virgin, Cathedral of Le Mans by Nicholas Coffetier and Louis Steinheil (1866-82); incorporating nineteenth-century Marian iconography, the ensemble seemed to contemporaries more Gothic in its formal and chromatic effect than work that was more authentic. By this date the religious and national symbolism of thirteenth-century Gothic was losing ground.Creation of new stained glass received a major impetus as a result of vandalism by revolutionaries and by cathedral chapters in the eighteenth century; new windows were ordered for bays from which the originals had long since disappeared or in which they had never existed. Glassworkers looked to Gothic models, consulting publications such as that of Fathers Cahier and Martin on the ensemble at Bourges, but chose to render freely an imagery pertinent to clergy, the faithful or the political ambition of patrons. Though the Office of Religion intervened more in connection with new designs than with restoration, it was often possible to circumvent their control. Cardinal de Bonald, who ordered the cycle on founders of the church in Lyon, sponsored without submitting to the Office important new designs on such subjects as Pope Gregory vii conferring the primateship of the Gauls to St. Gébuin, Archbishop of Lyon, in 1079. With other such examples they form part of a new and diverse iconographical corpus. The erroneous belief encouraged by “medievalists” that Gothic stained glass was oriented towards education of the people informed a choice of themes beyond those standard in Christian doctrine, emphasizing the medieval history and symbolism of the Church as witness of renewed power of the bishop. On the other hand, architects such as Viollet-le-Duc approached the installation of stained glass in an archaeological sense grounded in belief that unity of style had been achieved in the thirteenth century. After 1880 this archaeological understanding gave way to that of stained glass as pictorial form. Neo-Gothic stained glass came to an end when the conflicts between Church and State (law separating them in 1905) became unmanageable for both sides.